Diseño de un dispositivo ortésico funcional para apoyar los protocolos de rehabilitación de tenorrafia en mano. (2023)
This work presents the design of a hand tenorrhaphy rehabilitation device, using biomimicry as a method of innovation-creation, which gives rise to the concept of "biomimicry in design. Concept for soft hand rehabilitation." The objective of the project is to create an ergonomic, functional, and scalable device that allows for early and periodic passive mobilization of the fingers while immobilizing the wrist and proximal phalanges.